Tumor Volume Reduction Rate during Adaptive Radiation Therapy as a Prognosticator for Nasopharyngeal Cancer - Lee, Hyebin (Cancer Res Treat, 2016)
PURPOSE: The purpose of this study is to evaluate the prognostic significance of the tumor volume reduction rate (TVRR) measured during adaptive definitive radiation therapy (RT) for nasopharyngeal cancer (NPC). MATERIALS AND METHODS: We reviewed the RT records of 159 NPC patients treated with definitive RT with or without concurrent chemotherapy between January 2006 and February 2013. Adaptive re-planning was performed in all patients at the third week of RT. The pre- and mid-RT gross tumor volumes (GTVs) of the primary tumor and the metastatic lymph nodes were measured and analyzed for prognostic implications. RESULTS: After a median follow-up period of 41.5 months (range, 11.2 to 91.8 months) for survivors, there were 43 treatment failures. The overall survival and progression-free survival (PFS) rates at 5 years were 89.6% and 69.7%, respectively. The mean pre-RT GTV, mid-RT GTV, and TVRR were 45.9 cm(3) (range, 1.5 to 185.3 cm(3)), 26.7 cm(3) (1.0 to 113.8 cm(3)), and –41.9% (range, –87% to 78%), respectively. Patients without recurrence had higher TVRR than those with recurrence (44.3% in the no recurrence group vs. 34.0% in the recurrence group, p=0.004), and those with TVRR > 35% achieved a significantly higher rate of PFS at 5 years (79.2% in TVRR > 35% vs. 53.2% in TVRR ≤ 35%; p < 0.001). In multivariate analysis, TVRR was a significant factor affecting PFS (hazard ratio, 2.877; 95% confidence interval, 1.555 to 5.326; p=0.001). CONCLUSION: TVRR proved to be a significant prognostic factor in NPC patients treated with definitive RT, and could be used as a potential indicator for early therapeutic modification during the RT course.